Cervical lymphadenitis as a result of (Hijab) pin prick in north of Jordan - Gharaibeh, Mahmoud M.; Alwadiya, Ahmed; Gharaibeh, Ahmad (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Cervical lymph nodes are lymph nodes found in the neck. Hijab is a head cover worn by some Muslim women in the presence of any adult male outside of their immediate family, which usually covers the head, neck and chest. It is strictly forbidden to Muslim woman to unveil any single hair of her head, so they use many pins around the head to fix their Hijab. Often, while using pins they are self-pricked. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The main aim of our work is to reveal a new cause of lymphadenopathy, which is not known till now. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Retrospective study during the past five years among seventy-five female outpatients, visited our Oral and Maxillofacial clinic in dental department. Our data was collected according to medical history of patients; all female patients with cervical lymphadenopathy were using (A hijab). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Data collected of 75 female patients. Lymphadenopathy causes were various. Most of these causes resulted from nonspecific lymphadenitis (67 patients), 4 tuberculosis, 2 lymphoma, 2 cat scratch disease. Aetiology of 67 nonspecific lymphadenitis was 40 patients of dental cause, 10 of sore throat, 7 of acne vulgaris, 3 of mild facial injuries, and 7 of (Hijab pin pricks). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Hijab pin prick cervical lymphadenitis in Islamic communities is not uncommon and, unexplained cervical lymphadenitis should be considered as potential cause.